Effects of 1α‐Calcidol (Alfacalcidol) on Microvascular Endothelial Function, Arterial Stiffness, and Blood Pressure in Type II Diabetic Nephropathy Patients. (January 2016) - Munisamy, Seetha; Daud, Kamaliah M.; Mokhtar, Siti S.; Rasool, Aida H.G
Abstract: Objectives: To determine the effects of six months alfacalcidol on microvascular endothelial function, arterial stiffness, and BP in DN patients. Methods: Twenty‐eight DN patients on alfacalcidol, 0.25 μ g daily for six months were compared to 32 controls on conventional treatment. Measurements of microvascular endothelial function, arterial stiffness [AIx and PWV], hsCRP, and BP were performed; differences between baseline and six months treatment were evaluated. Results: No difference was seen in microvascular endothelial function for both groups after six months. Improvement in CSBP ( p = 0.027) with trends of improvement in AIx ( p = 0.063), PWV ( p = 0.075), and systolic BP ( p = 0.088) were seen in the alfacalcidol group with no changes observed in controls. Subgroup analysis of alfacalcidol group showed that vitamin D‐deficient patients had better response to treatment. hsCRP level remained unchanged in alfacalcidol group; significant increase was however seen in controls. Conclusion: Alfacalcidol did not have an effect on microvascular endothelial function in DN patients. Alfacalcidol significantly improved CSBP with trends of improvement in arterial stiffness and peripheral BP. Alfacalcidol appears to be more beneficial in vitamin D‐deficient patients.